Effective personality preferences of software programmer: A systematic review - Gilal, A.R. (Institute of Information Science, 2017)
A plethora of research has been carried out to explore the key importance of team roles and personality types in software development. What types of personality are handy and beneficial for an ideal and effective teamwork is still a question for the researchers and practitioners. This study has combined the past claims of personality preferences for programmer role so that researchers and practitioners can easily access the literature. In order to achieve the study objective, Kitchenham guidelines were followed to design and implement the review protocol. The whole review focused to find the effective personality preferences of programmer role from different experimental settings: individuals-Andteams and academic-And-industry. Additionally, only those studies were selected that used Myers-Briggs type indicator (MBTI) personality test. The results of this study were divided into three categories based on the obtained personality preferences: strongly appeared, weakly appeared, and disappeared. For example, it was strongly observed in the results that combination of intuitive (N) and feeling (F) traits is not a suitable personality choice for programmer role. The conclusion of this study can be drawn with the statement that personality based software development research needs serious attention to fill the wide gaps. There are numerous ambiguities for practitioners if they intend to put these studies into use.